2023
DOI: 10.3389/fpubh.2023.1205159
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of four vaccines in preventing SARS-CoV-2 infection in Almaty, Kazakhstan in 2021: retrospective population-based cohort study

Abstract: BackgroundIn February 2021 Kazakhstan began offering COVID-19 vaccines to adults. Breakthrough SARS-CoV-2 infections raised concerns about real-world vaccine effectiveness. We aimed to evaluate effectiveness of four vaccines against SARS-CoV-2 infection.MethodsWe conducted a retrospective cohort analysis among adults in Almaty using aggregated vaccination data and individual-level breakthrough COVID-19 cases (≥14 days from 2nd dose) using national surveillance data. We ran time-adjusted Cox-proportional-hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…We found that less than half of providers believed in safety and effectiveness of the most common COVID-19 vaccines available in Kazakhstan at that time. Low trust in COVID-19 vaccine safety and effectiveness could have been influenced by the lack of published data on the predominant COVID-19 vaccines available in Kazakhstan, Sputnik V, and QazVac (43)(44)(45). Most literature on COVID-19 vaccines was predominantly in English, as are most scientific publications, and therefore likely not easily accessible to the majority of healthcare providers in Kazakhstan (46), where 97% of the population speaks Russian and 80% speaks Kazakh (47).…”
Section: Knowledge About Vaccines and Confidencementioning
confidence: 99%
“…We found that less than half of providers believed in safety and effectiveness of the most common COVID-19 vaccines available in Kazakhstan at that time. Low trust in COVID-19 vaccine safety and effectiveness could have been influenced by the lack of published data on the predominant COVID-19 vaccines available in Kazakhstan, Sputnik V, and QazVac (43)(44)(45). Most literature on COVID-19 vaccines was predominantly in English, as are most scientific publications, and therefore likely not easily accessible to the majority of healthcare providers in Kazakhstan (46), where 97% of the population speaks Russian and 80% speaks Kazakh (47).…”
Section: Knowledge About Vaccines and Confidencementioning
confidence: 99%
“…Vaccination started in February 2021, and mandatory vaccination was required for health providers, teachers of secondary schools, and police officers; then, as access to vaccines expanded, it became compulsory for students and employees of higher and secondary educational institutions. Several types of vaccines were available to the public: Kazakhstan’s QazVac, Russian Sputnik V and Sputnik Lite, Chinese Hayat-Vax (Sinopharm) and CoronaVac, and later Pfizer’s Comirnaty vaccine (USA) for vaccination of adolescents, pregnant women and patients of maternity wards [ 14 ]. It is commonly accepted that several types of vaccines allow for more rapid collective immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from late 2020, this vaccine has been used in 71 countries spanning Latin America, Africa, and Asia, including Kazakhstan. Between February and September 2021, Kazakhstan’s COVID-19 vaccination initiative predominantly utilized Gam-COVID-Vac, with over 85% of vaccine recipients having been administered Sputnik-V [ 8 ]. During this extensive vaccination rollout, we embarked on a study to assess the safety, potential side effects, and immune reactions to Gam-COVID-Vac among a group with varied prior exposure to COVID-19 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%